Large Igneous Provinces and the repositioning of South American protocratons in Columbia in the Orosirian-Statherian Transition - Chaves, Alexandre de Oliveira; Fonseca, Wellison Martins (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2017)
Based on the orogenic and intraplate tectonic processes existing during Orosirian (2,05-1,80 Ga) – Statherian (1,80-1,60 Ga) transition, this article is an attempt to reposition the South American proto-cratons Amazon, São Francisco, Rio de la Plata and São Luís in Columbia supercontinent using geological, geochronological and paleomagnetic data of Large Igneous Provinces (LIP) and Silicic Large Igneous Provinces (SLIP) available in the literature. With the proto-craton Rio de la Plata turned upside down between Amazon and Baltica and through a clockwise rotation of about 90 degrees of the proto-craton Amazon in relation to its current position by placing it side by side with proto-craton San Francisco, a possible triple junction can be reconstructed, in which their LIP and SLIP are accommodated in time and space. A geological setting consistent with the Statherian Taphrogenesis, which marks the beginning of the Columbia breakup, is reconstructed from the tectonic evaluation here proposed.
Keywords: LIP; Columbia; South America; Tectonic reconstruction; Orosirian-Statherian